2005
DOI: 10.1200/jco.2005.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin for Women With Ovarian Carcinoma After Treatment With Platinum and Taxanes Fails

Abstract: Trabectedin administered as a 3-hour infusion at 1,300 microg/m(2) is a safe new drug with promising activity in relapsed ovarian cancer, showing a 43% objective response rate in patients with platinum-sensitive disease, which favorably compares with other salvage treatments and warrants additional development either alone or in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
94
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 23 publications
4
94
1
2
Order By: Relevance
“…Confirmation of these early results has been seen in the recently completed every 3 week regimen two arm randomised ET-743:B-026 study (Del Campo et al, 2006;McMeekin et al, 2007). The results of the present study and those reported by Sessa et al (2005), Del Campo et al (2006), andMcMeekin et al (2007) demonstrate the effectiveness of trabectedin as a single agent in the platinum-sensitive patient population with respect to ORR and disease stabilisation. The most common TEAE in the three studies was a self-limiting reversible elevation in liver enzymes, with noncumulative myelosuppression being a secondary common adverse event.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Confirmation of these early results has been seen in the recently completed every 3 week regimen two arm randomised ET-743:B-026 study (Del Campo et al, 2006;McMeekin et al, 2007). The results of the present study and those reported by Sessa et al (2005), Del Campo et al (2006), andMcMeekin et al (2007) demonstrate the effectiveness of trabectedin as a single agent in the platinum-sensitive patient population with respect to ORR and disease stabilisation. The most common TEAE in the three studies was a self-limiting reversible elevation in liver enzymes, with noncumulative myelosuppression being a secondary common adverse event.…”
Section: Discussionsupporting
confidence: 86%
“…The efficacy results seen in all platinum-sensitive patients treated every 3 weeks with trabectedin in the SENDO study (Sessa et al, 2005) showed a response rate of 43.5% (95% CI: 23 -65%) with TTP of 7.9 months (95% CI: 7.5 -14.1 months). Similarly, the ET-743:B-026 study (Del Campo et al, 2006) showed a response rate of 37.4% (95% CI: 28.2 -47.3%) with TTP of 6.8 months (95% CI: 5.5 -7.4 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ET-743 is a tetrahydroisoquinoline alkaloid isolated from the Caribbean sea squirt Ecteinascidia turbinata (12), pointing to marine products as a potential new source of molecules with original chemical structures and activities. ET-743 shows a broad activity spectrum toward tumor cell lines at pM and low nM concentrations (6,13) and has clinical activity toward ovarian cancer as well as soft tissue and bone sarcomas in heavily pretreated patients (14)(15)(16). In particular, ET-743 treatment is associated with a striking, long-term response in a subset of patients with otherwise chemoresistant soft tissue sarcomas (reviewed in ref.…”
mentioning
confidence: 99%